1993
DOI: 10.1002/jcu.1870210306
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of capsular morphology in normal and traumatic ankle joints

Abstract: Ultrasonography was used to inspect the ankle anatomy of 20 healthy volunteers. The images produced were correlated with anatomical structures by examining three dissected cadaver ankles. The anterolateral pouch of the articular capsule was identified by ultrasonography in 91% of the normal ankle joints as a hypoechoic area. The posterolateral pouch of the articular capsule also could be identified by ultrasonography as a hypoechoic area in 84% of the normal ankles examined. The lateral aspect of 105 traumatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 8 publications
2
19
0
1
Order By: Relevance
“…28 Nazarian et al disclosed fluid in the anterior recess of the ankle joint in 33% of subjects examined. 29 In addition to our findings and those of two other studies, 28 30 Nazarian could not detect fluid in the posterior recess. In contrast, their study found retrocalcaneal bursal fluid in 50% of subjects, compared with 24% in our findings.…”
Section: Discussionsupporting
confidence: 78%
“…28 Nazarian et al disclosed fluid in the anterior recess of the ankle joint in 33% of subjects examined. 29 In addition to our findings and those of two other studies, 28 30 Nazarian could not detect fluid in the posterior recess. In contrast, their study found retrocalcaneal bursal fluid in 50% of subjects, compared with 24% in our findings.…”
Section: Discussionsupporting
confidence: 78%
“…A few studies have tried to characterize synovial fluid volume and distribution in normal as well as pathologic ankle joints that can be visualized with ultrasonography and magnetic resonance imaging 1245. Through the use of ultrasound, Schmidt et al characterized the physiologic normal volumes of the human ankle joint without any fluid being introduced into the joint 4.…”
Section: Discussionmentioning
confidence: 99%
“…Several radiographic studies have attempted to characterize the volume of synovial fluid in both normal and pathologic ankle joints through magnetic resonance imaging and ultrasonography 15. However, these studies have generally commented on relative sizes between normal and pathologic ankle joints and have not characterized the actual volume or pressures inside the joints.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with MRI, diagnostic ultrasound is useful but less accurate and sensitive in detecting acute lateral ankle ligamentous injury. 13,16,17 Evidence Category: B 12. Arthrography and tenography are less accurate than MRI and CT, especially when performed 48 hours after lateral ligamentous injury.…”
Section: Diagnosismentioning
confidence: 99%
“…For ultrasound versus MRI, accuracy was 95% and 100%, and sensitivity was 50% and 100%, respectively. Other authors 16,17 who compared ultrasonography for acute ankle injuries with surgical findings have shown accuracy ranging from 90% to 100% for both the ATFL and CFL.…”
mentioning
confidence: 99%